Delivering infrastructure and land use - transport integration policy: Examining good governance issues in Melbourne and Perth - Legacy, C.; Sturup, S.; Curtis, Carey; Wigan, M. (Published in conference proceedings and on CD, 2009)
Governance is a difficult topic to address in the often controversial area of transport and planning. Good governance allows issues associated with balancing different interests, objectives and pressures, to be addressed and solved - but its absence is a major barrier to this occurring. The Australasian Centre for the Governance and Management of Urban Transport, an independent research centre, held two forums in 2008 to discuss infrastructure governance in Melbourne, and transport and land use integration in Perth, Australia. The forums were structured to enable practitioners from a range of agencies and individuals from the community to share their experience and viewpoints on good governance. Issues presented were interrogated collectively during breakout group discussions affording participants a chance to also express their positions and to raise issues. The diversity of attendees permitted a wide range of views on governance. This paper examines the key differences which distinguished the perceptions and practice of good governance in Melbourne and Perth and identifies socio-political reasons why these differences exist.Analysis of the discussions from the forums in Melbourne and Perth reinforced the hypothesis that different governance frameworks were in use in each of these two cities. While transparency, communication structures and resource constraints remained consistent issues in both cities, the emergent differences raised questions about how and if institutional structures and procedures facilitated and mediated the implementation of policy.